Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

Quadratic equations: Solve for x: X4 - 5X2 + 4 = 0

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SEE EXPERT ANSWER

To see the expert answer you'll need to create a free account at Brainly

In quadratic form, the equation would be -5x2 + x4 + 4 = 0
Wouldn´t this equation written in this way x^4-5x^2+4=0
?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

But you would have to have the equation in ax^2 + bx + c form
If this equation has the form above so try to factor out.
-5x2 + x4 + 4 = 0. From here you can use (x^2-4)(x^2-1);
Reminder if ab=0 then a=0 or b=0
X^4-5X^2+4=0 Substitute u=X^2 into the equation. This will make the quadratic formula easy to use. u^2-5u+4=0 u=X^2 Move -4 to the left-hand side of the equation by adding it to both sides. The goal is to have all terms on the left-hand side equal to 0. u^2-5u+4=0 In this problem -1*-4=4 and -1-4=-5, so insert -1 as the right hand term of one factor and -4 as the right-hand term of the other factor. (u-1)(u-4)=0 Set each of the factors of the left-hand side of the equation equal to 0. u-1=0 u-4=0 Since -1 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 1 to both sides. u=1 u-4=0 Set each of the factors of the left-hand side of the equation equal to 0. u=1 u-4=0 Since -4 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 4 to both sides. u=1 u=4 The complete solution is the set of the individual solutions. u=1, 4 Substitute the real value of u=X^2 back into the solved equation. X^2=1 X^2=4 Solve the first equation for X. X^2=1 Take the square root of both sides of the equation to eliminate the exponent on the left-hand side. X=+/-sqrt(1) Pull all perfect square roots out from under the radical. In this case, remove the 1 because it is a perfect square. X=+/-1 First, substitute in the + portion of the +/- to find the first solution. X=1 Next, substitute in the - portion of the +/- to find the second solution. X=-1 The complete solution is the result of both the + and - portions of the solution. X=1,-1 Solve the second equation for X. X^2=4 Take the square root of both sides of the equation to eliminate the exponent on the left-hand side. X=+/-sqrt(4) Pull all perfect squXre roots out from under the radical. In this case, remove the 2 because it is a perfect square. X=+/-2 First, substitute in the + portion of the +/- to find the first solution. X=2 Next, substitute in the - portion of the +/- to find the second solution. X=-2 The complete solution is the result of both the + and - portions of the solution. X=2,-2 The solution to X^4-5X^2+4=0 is X=1,-1,2,-2. X=1,-1,2,-2
Two different ways of solving but the same answer.

Not the answer you are looking for?

Search for more explanations.

Ask your own question